Broken solidarities : how open global governance divides and rules - Anderl, Felix (Bristol Studies in International Theory., 2022)
Felix Anderl's book is a stimulating analysis of the decline of the social movement against the World Bank and the rise of a new form of transnational rule. The book observes international organizations and social movements in their interaction, demonstrating how social movements are divided and ruled in the absence of a ruler.